Etiology and Long‐Term Outcome of Patients Undergoing Pericardiocentesis. Issue 12 (23rd December 2017) - Strobbe, Alexander; Adriaenssens, Tom; Bennett, Johan; Dubois, Christophe; Desmet, Walter; McCutcheon, Keir; Van Cleemput, Johan; Sinnaeve, Peter R
Abstract : Background: Pericardial effusions can be caused by a variety of disorders. The frequency of the underlying diseases varies with patient population; therefore, previously reported series are not necessarily representative of other populations. Our purpose was to examine the etiology of pericardial effusions and the survival of patients requiring pericardiocentesis at a tertiary center. Methods and Results: We performed a retrospective observational study of 269 consecutive patients who underwent percutaneous pericardiocentesis at our university hospital between 2006 and 2016 and had prospective follow‐up for up to 10 years. The most frequent etiologies were idiopathic (26%), malignancy (25%), and iatrogenicity (20%), whereas bacterial causes were very rare. The most frequent malignancies originated from the lung (53%) or breast (18%). A new cancer was diagnosed with malignant pericardial effusion as the presenting complaint for 9% of patients, whereas the pericardium was the first metastatic site of a known malignancy in 4% of patients. Survival was significantly poorer in malignancy‐related versus non–malignancy‐related effusions ( P <0.001) and in cytology‐positive versus cytology‐negative effusions in the overall cohort ( P <0.001). Among cancer‐only patients, however, there was no significant difference in long‐term survival between cytology‐positive and ‐negative effusions. Conclusions: In this contemporary tertiary‐center cohort, pericardial effusions often represent the primary instance of a new malignancy, underscoring the importance of cytological analyses of noniatrogenic effusions in patients without known cancer, as survival is significantly worse. In cancer patients, however, the presence of pericardial malignant cytology does not appear to affect outcome significantly.